Особенности использования комбинированного протяжного инструмента для обработки внутренних полостей крупных чугунных цилиндров - Розенберг, О.А.; Студенец, С.Ф.; Мельниченко, В.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
In article problems of using of combined broaching tool for treatment internal cylindrical hollows in the big size cylinder from special irons. The results of examinations of process cuttingdeforming broaching of big orifices (diameter 261 mm) in details from special irons have been represented.